The Teaching of English in Indonesian Primary Schools: a Response to the New Policy - Ahmad Jazuly; Ninuk Indrayani; Nostalgianti Citra Prystiananta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
In this study, I investigated the teachers' current practice without curriculum of English lesson at primary schools and teacher's response to the new policy on English lessons in primary school. The participants of this study were 46 respondents which consist of 17 males and 29 females. The data was obtained by distributing an open-ended question to teachers who teach in a primary school in Jember district of East Java. The questionnaire was administered to the teacher to be filled in directly. The first finding showed that most of the teachers agreed that teachers should be qualified, teachers need appropriate teaching media for students, and most of the students are very enthusiastic in learning English. The second finding about the teacher's response to the new policy on English lessons in primary school showed that most teachers expected the government to return the English language policy to be taught in primary school as a compulsory subject. Conclusion, the current practices of teaching English in primary school are divided into three parts, 1) most the teachers who involve become sample in this study agreed that the teachers should be qualified in teaching English in primary school, 2) most the teachers needed teaching media appropriate for the students in primary school, 3) most the students were very enthusiastic about learning English. Keyword; Indonesian primary school, teacher, new policy.